Kontekstualisasi Penafsiran Ayat-Ayat Tarbawi Dalam Pengasuhan Pesantren - Ade Nurhayat (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
This study aims to comprehensively explore the contextualization of the interpretation of the tarbawȋ verses in the care of Islamic boarding schools and the ideal care of Islamic boarding schools using qualitative research types with library research and conceptual thematic methods (maudu’i). The primary data sources used are the Qur'an and secondary data sources from books, books and other literature that support the research theme. Data were collected through library studies. The researcher then analyzed the tarbawi verses in the Qur'an that are relevant to the theme of the care of Islamic boarding schools, then analyzed the interpretation of the tarbawi verses by referring to classical and contemporary tafsir books. The results of the study indicate that the contextualization of the interpretation of the tarbawi verses in the care of Islamic boarding schools is the obligation to study in Islamic boarding schools as an analysis of the contextualization of tafaqquh fi ad-Di>n surah At-Taubah [9]: 122, the Curriculum of Islamic Boarding School Care as a contextualization of Surah Luqman [31]: 13-19, Parenting pays attention to the development of santri ethics as a contextualization of surah Al-Mujadalah [58]: 11, Intellectual and Spiritual Integration in Parenting in Islamic Boarding Schools is a Contextualization of Surah Fatir [35]: 28, Criteria for Ideal Parenting analysis of surah Ali ‘Imran [3]: 79, Building effective communication is the key to success in parenting students as a contextualization of surah Al-Ahzab [33]: 70-71. In addition, this study offers 5 points related to ideal Islamic boarding school parenting, namely: having components of Islamic boarding school parenting, objectives of Islamic boarding school parenting, Islamic boarding school parenting curriculum, patterns of Islamic boarding school parenting and ideal caregivers. Keywords: Ayat-ayat of Tarbawi; Contextualization; Islamic Boarding School Parenting